Changes in Glomerular Filtration Rate and Its Relation to Serum Calcium Level in Advanced Stages of Chronic Kidney Disease - Saha, Gobinda Chandra; Akhtaruzzaman, M; Mustafa, Ekramul; Mahmud, Asif; Sikder, Sunil Kumar (Journal of National Institute of Neurosciences Bangladesh, 2015)
Background: The progression of CKD occurs in five different stages in which there are gradual changes of GFR, serum creatinine and serum calcium. Objective: The study was undertaken to determine GFR in advanced stages of CKD and its relation with s. creatinine and s. calcium and also to find out the correlation between s. creatinine and s. calcium. Methodology: This study was carried out in the departments of Physiology and Nephrology, Rajshahi Medical College. All the advanced stage chronic kidney disease patients were taken as comparison. Apparently healthy persons were taken as control. Serum Creatinine was measured by alkaline picrate method; estimation of GFR was done by using Cockcroft- Gault formula and serum calcium was performed by analyzer. Result: In this study a total number of 120 subjects were included, out of which 30 were healthy control and 90 were diagnosed cases of advanced stages of CKD. Among the patients, 55 (61.12%) were male and 35 (38.88%) were female. Mean age (±SD) of the patients were 45 ± 11.16 (Range 20-65 years). While comparing between groups of CKD patients, it was found that s. creatinine of control group was significantly lower than that of group 1. Again s. creatinine of Group 1 was significantly lower than that of group 2 and similarly, s. creatinine of group 2 was significantly lower than that of group 3. On the other hand, s. calcium of control group was significantly higher than group 1, likewise s. calcium of group 1 was significantly higher than that of group 2 and s. calcium of group 2 was significantly higher than that of group 3. Conclusion: From this study the inference could be drawn that serum calcium had a positive correlation with GFR and a negative correlation with s. creatinine. J. Natl Inst. Neurosci Bangladesh 2015;1(1):15-17